Reconstruction of baseline time-trace under changing environmental and operational conditions. (22nd February 2016) - Aryan, P; Kotousov, A; Ng, C T; Wildy, S
Abstract: Compensation of changing environmental and operational conditions (EOC) is often necessary when using guided-wave based techniques for structural health monitoring in real-world applications. Many studies have demonstrated that the effect of changing EOC can mask damage to a degree that a critical defect might not be detected. Several effective strategies, specifically for compensating the temperature variations, have been developed in recent years. However, many other factors, such as changing humidity and boundary conditions or degradation of material properties, have not received much attention. This paper describes a practical method for reconstruction of the baseline time-trace corresponding to the current EOC. Thus, there is no need for differentiation or compensation procedures when using this method for damage diagnosis. It is based on 3D surface measurements of the velocity field near the actuator using laser vibrometry, in conjunction with high-fidelity finite element simulations of guided wave propagation in free from defects structure. To demonstrate the feasibility and efficiency of the proposed method we provide several examples of the reconstruction and damage detection.